Perubahan Pola Sakramen Umat Katolik Bandung Pada Era Pandemi Covid-19 - R.F. Bhanu Viktorahadi (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2021)
During the Covid-19 pandemic, Catholics in Bandung had difficulty understanding the Sacrament as a means and sign of salvation from God. This difficulty arises because people can only follow and celebrate the Sacraments, especially the Eucharist or Mass online. The absence of direct encounter causes reduction and degradation of appreciation of the efficacy or effectiveness of online Masses as a means and a sign of safety. People desperately need a program that can increase their understanding of the Sacrament's efficacy, especially online Mass. For this reason, the Center for Philosophy, Culture and Religious Studies, Faculty of Philosophy, Parahyangan Catholic University (CPCReS FF UNPAR) Bandung, in collaboration with the Theological Science Community (KBI) Faculty of Philosophy UNPAR, held an Extention Course Theology (ECT). The program that uses the dialogue method is followed by Catholics in Bandung online by involving speakers with theological backgrounds from FF UNPAR. The evaluation results show that the material from this course can increase understanding of the efficacy of the sacrament, especially in this Pandemic era.